2014
DOI: 10.1155/2014/981893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Stromal Demarcation Line after Two Different Protocols of Accelerated Corneal Collagen Cross-Linking Procedures Using Anterior Segment Optical Coherence Tomography and Confocal Microscopy

Abstract: Purpose. To evaluate the depth of corneal stromal demarcation line using AS-OCT and confocal microscopy after two different protocols of accelerated corneal collagen cross-linking procedures (CXL). Methods. Patients with keratoconus were divided into two groups. Peschke CXL device (Peschke CCL-VARIO Meditrade GmbH) applied UVA light with an intended irradiance of 18.0 mW/cm2 for 5 minutes after applying riboflavin for 20 minutes (group 1) and 30 minutes (group 2). One month postoperatively, corneal stromal dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
1
12
0
4
Order By: Relevance
“…Similar to our observation, studies comparing the demarcation line depth between conventional and accelerated CXL showed that the demarcation line was consistently deeper with the former protocol . Kymionis et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our observation, studies comparing the demarcation line depth between conventional and accelerated CXL showed that the demarcation line was consistently deeper with the former protocol . Kymionis et al .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our observation, studies comparing the demarcation line depth between conventional and accelerated CXL showed that the demarcation line was consistently deeper with the former protocol. [28][29][30] Kymionis et al noted that a 10-min treatment with 9 mW/cm 2 resulted in a demarcation line that was less deep compared to the standard protocol. 29 In a latter study, Kymionis and his co-workers developed a modified 9 mW/cm 2 -accelerated CXL protocol by increasing the treatment time to 14 min resulting in 40% increased of total illumination energy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing dextran–riboflavin soaking time, deeper demarcation lines were found after 30 min than 20 min (Ozgurhan et al. ). Due to a higher intracorneal concentration of riboflavin with time, this probably means that a higher intrastromal concentration of riboflavin causes a deeper effect (Ehmke et al.…”
Section: Discussionmentioning
confidence: 99%
“…Trotz der bereits berichteten großen Datenmenge, gab es zu diesem Zeitpunkt nur 7 [110][111][112][113][114][115][116] bzw. 12 [117][118][119][120][121][122][123][124][125][126][127][128] randomisierte Studien, in denen ein Vergleich zwischen dem Dresden-Protokoll und einer unbehandelten Kontrollgruppe bzw. anderen Protokollen durchgeführt wurde.…”
Section: Grundlagen Des Crosslinkingsunclassified